Diagenesis of Upper Jurassic concretions from the Antarctic Peninsula - Kießling, Wolfgang; et al. (Journal of Sedimentary Research, 2001)
Early-diagenetic calcite concretions are widespread in mudstone-tuff sequences deposited in Late Jurassic oxygen-deficient basins of the Antarctic Peninsula. Although obscured or destroyed in host rocks, original components and sedimentary structures are well preserved in concretions, in spite of significant mineralogical and geochcmical change during growth. Early diagenesis led to a rapid and almost total variation in the mineralogy within the concretions, independently of the original host lithologies. Siliceous particles were replaced by chlorite and zeolites in suboxic, alkaline, and moderately reducing conditions on the sea floor and in the first centimeters of burial. These conditions also led to localized early formation of phosphate concretions. Pyrite developed subsequently because of high sulfide abundance in the sulfate reduction zone. Most calcite precipitation took place in the lower part of the sulfate reduction zone in a strongly alkaline environment where sulfide content had been lowered by pyrite precipitation. In this stage, the remaining siliceous elements were dissolved or replaced by calcite. Later diagenetic changes include enlargement of zeolites, minor changes in clay minerals, and the formation of calcite veins. The wide range of δ 13C values in cement and vein calcite (-1.4‰ and -20.23‰ PDB) is explained by mixed carbon sources from organic matter oxidation and dissolution of calcareous shells. The low δ 18O of calcite (-2.34‰ to -19.72‰ PDB) is the result of recrystallization in contact with high-temperature diagenetic or hydrothermal fluids flushed through micro-fractures in the concretions, which also produced extensive vein formation. Copyright © 2001, SEPM (Society for Sedimentary Geology).
UnivIS-Import:2015-03-09:Pub.2001.nat.dgeo.IGM.LP.diagen